Gender-differentiated impacts of a Rural Electrification Policy in Nigeria. (March 2022) - Cicowiez, Martin; Akinyemi, Opeyemi; Sesan, Temilade; Adu, Omobola; Sokeye, Babajide
Abstract: This paper investigates the potential impacts of the Nigerian Rural Electrification Fund (REF-1) on the development of rural communities and specifically assesses the policy's differential impacts on men and women's employment and income. It examines the best approach for the implementation of the subsidy grant that promotes economic activities in the rural areas, in line with the objective of the policy. To that end, a gendered Computable General Equilibrium (CGE) model was employed and data were analyzed under four scenarios against a baseline scenario. The results indicate that as the rural electrification fund increases energy supply, market employment for women, factor incomes, and output in the agricultural sector also rises. Also, the scenario where the subsidy grant was combined with labour and factor productivity, recorded the largest increase overall. The policy implication of these results is that a policy complementary approach is needed to achieve the goals highlighted in the Nigerian Rural Electrification Strategy policy and to produce the desired economic outcomes. In other words, the government subsidy grants on its own to expand electricity supply in the rural areas is not sufficient, it will need to be complemented with policies that enhances productivity and efficiency. Highlights: Increasing rural electrification is vital for rural economic development Gender-differentiated impacts of policies are key to effective implementation Subsidy for rural electrification program increases rural women economic outcomes The subsidy grant alone is not sufficient to promote rural development in Nigeria Policies that enhance efficiency and productivity guarantees optimal outcome